Islamic art and architecture in a contested region: Negotiating the Muslim Heritage in Meskheti, Georgia - KANÇAL, NİCOLE SİLVİA (My University, 2022)
© 2022 Intellect Ltd Article.This article draws upon fieldwork carried out in the Meskheti (Ahiska) region of modern Georgia to introduce, analyse, and discuss local mosque architecture. The region\"s Islamic art and architecture is largely unknown to the international scholarly community due to a turbulent history, especially in the twentieth century. However, as I show, these mosques shed light on trans-regional and trans-imperial artisan and patronage networks and architectural and aesthetic currents in the nineteenth and early twentieth centuries. Also of interest is the story of how local Muslim communities navigated the complex process of maintaining their religious identity and visible material culture amid the shifting political and social tides in the region during that time, and the fate of the edifices they built after they were forced to leave the region in the mid-twentieth century. Today, much of the Islamic material heritage of Meskheti, Georgia remains under threat. I conclude by considering the current situation of the preservation of historical edifices and offer thoughts on the problems that must be overcome.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Meskheti; Ahiska; Ottoman Georgia; Ottoman architecture; Georgian Muslims; Black Sea Region; Ahıska; Black Sea Region; Georgian Muslims; Meskheti; Ottoman architecture; Ottoman Georgia